RACISM ON SOCIAL NETWORKS AND BRAZILIAN MEDIA: ANALYSIS OF DISCOURSES AND SOCIAL IMPACTS (REMUNOM, 2026)
Racism is a structural phenomenon present in Brazilian society and is also significantly manifested in the digital environment. With the expansion of social networks and digital media, these spaces have facilitated the circulation of information but have also become environments conducive to the reproduction of discriminatory discourses, both explicitly and implicitly. In this context, this article aims to analyze manifestations of racism on social networks and Brazilian media, as well as their social and legal impacts. The research was developed using a qualitative and quantitative approach, based on an interdisciplinary literature review, content analysis of publications on digital platforms widely used in Brazil, and a legal analysis of cases related to racism in the digital environment. The results indicate the persistence of racial hate speech, often normalized in public debate and intensified by the operational dynamics of digital platforms. Such discourses directly affect the Black population and other racialized groups, producing significant social impacts. Although the Brazilian legal system includes provisions aimed at combating racism, their application in the digital environment still faces challenges, such as difficulties in identifying those responsible and limitations in content moderation policies. Therefore, it is concluded that addressing racism on social networks requires integrated measures involving public policies, education for the critical use of digital media, and the improvement of legal accountability mechanisms, in order to promote a fairer and more inclusive virtual environment.